The Impact of Handover of the Watchkeeping in Supporting Shipping Safety on MV. Cemcon: Analisis Pengaruh Serah Terima Tugas Jaga dalam Mendukung Keselamatan Pelayaran di KM. Cemcon - Kurnia, Rahmat; Nurmala, Eka; Baihaqi, Baihaqi; Dahlan, Harris R.; Afdhal, M. (ATRIA: Jurnal Multidisiplin Riset Ilmiah, 2025)
The shipping industry plays an important role in supporting the global economy, especially in the distribution of goods between islands and countries. This study will not only provide an overview of the conditions of the handover of guard duties on MV. Cemcon but also recommendations that can be applied to improve shipping safety in the future. Thus, the background of this study provides a strong foundation for efforts to improve shipping safety through improving the handover process of guard duties. This study is a descriptive qualitative study. The results of this study are: 1) Ship handover procedures on MV. Cemcon includes handover preparation, communication between officers on watch, physical and visual checks, confirmation and signing, initial supervision; and 2) Implementation of handover of guard while sailing on MV. Cemcon includes preparation before handover, information handover process, joint checks, documentation and signatures, and initial monitoring by new officers.